2005
DOI: 10.1074/jbc.m408715200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Class A Scavenger Receptor Is Enhanced by High Glucose in Vitro and under Diabetic Conditions in Vivo

Abstract: In the early stage of atherosclerosis, macrophages take up chemically modified low density lipoproteins (LDL) through the scavenger receptors, leading to foam cell formation in atherosclerotic lesions. To get insight into a role of the scavenger receptors in diabetes-enhanced atherosclerotic complications, the effects on class A scavenger receptor (SR-A) of high glucose exposure in vitro as well as the diabetic conditions in vivo were determined in the present study. The in vitro experiments demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 45 publications
1
63
2
Order By: Relevance
“…In parallel, the expression of SR-A, which also showed a tendency towards decreased levels in the high-AGE diet-fed group, seems to contribute to the decreased clearance of AGEs, thus promoting AGE-related complications. Although SR-A-related published data are still controversial since high glucose or modified LDL are able to increase the expression of SR-A (Lam et al 2004, Fukuhara-Takaki et al 2005, while TNFa is able to decrease it in macrophages (Hsu et al 1996), even these in vitro or in vivo data cannot be compared to the peripheral monocytic SR-A expression and have a lot of differences to the AGEs receptors' regulation in the dietary glycotoxins model that we performed here. Another novel finding of this study is the possible link between the expression of scavenger receptors, such as RAGE, and the hormonal dysregulation of the female reproductive system, since the monocytic expression of RAGE was negatively correlated with testosterone levels and positively correlated with progesterone levels.…”
Section: Discussionmentioning
confidence: 65%
“…In parallel, the expression of SR-A, which also showed a tendency towards decreased levels in the high-AGE diet-fed group, seems to contribute to the decreased clearance of AGEs, thus promoting AGE-related complications. Although SR-A-related published data are still controversial since high glucose or modified LDL are able to increase the expression of SR-A (Lam et al 2004, Fukuhara-Takaki et al 2005, while TNFa is able to decrease it in macrophages (Hsu et al 1996), even these in vitro or in vivo data cannot be compared to the peripheral monocytic SR-A expression and have a lot of differences to the AGEs receptors' regulation in the dietary glycotoxins model that we performed here. Another novel finding of this study is the possible link between the expression of scavenger receptors, such as RAGE, and the hormonal dysregulation of the female reproductive system, since the monocytic expression of RAGE was negatively correlated with testosterone levels and positively correlated with progesterone levels.…”
Section: Discussionmentioning
confidence: 65%
“…Profound changes were observed in the expression of scavenger receptors. Of relevance is the up-regulation of MSR1 and SCARF1, because these molecules functions as endocytic receptors for acetylated LDL and may thus be implicated in lipidloaded foam cell formation contributing to atherosclerotic plaques development (50). Consistent with the view that hypoxia may exert a pathogenetic role in atherosclerosis and Alzheimer's disease (9,10,41) is also the down-regulation of CD163 and STAB1 scavenger receptors, which are endowed with atheroprotective activity (51,52), and of various genes involved in the regulation of fatty acid and/or cholesterol biosynthesis/transport and acting as antiatherogenic factors, e.g., LDLR, ApoE, and CYP27A1 (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SR-A expression is frequently observed in atherosclerotic lesions (Naito et al, 1992). Recent work has shown that exposure to high glucose in vitro enhances SR-A expression in human MDMs, accounting for the high incidence of atherosclerosis in diabetic patients (Fukuhara-Takaki et al, 2005). SR-A expression is also up-regulated by interferon-ïĄ, providing a possible explanation for the high risk of atherosclerosis in patients with systemic lupus erythematosus (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%